Endogenous Fungal Endophthalmitis in a Patient After Fetal Reduction Surgery With a Literature Review: A Case Report - Cao X; Jia P; Zhao L; Qiao X; Duan Y; Jia J; Xin J (Infection and Drug Resistance)
Xiaolu Cao,1 Peipei Jia,1 Lili Zhao,2 Xiulian Qiao,1 Yu Duan,1 Junxiao Jia,1 Jiangbo Xin1 1Hebei Ophthalmology Key Lab, Hebei Eye Hospital, Xingtai, Hebei, People’s Republic of China; 2Department of Pharmacy, First Hospital of Qinhuangda, Qinhuangdao, Hebei, People’s Republic of ChinaCorrespondence: Xiaolu Cao, Email 1299741546@qq.comAbstract: Endogenous fungal endophthalmitis (EFE) is a rare but severe ophthalmic emergency that often results in vision-threatening complications and, in extreme cases, can be life-threatening. This report presents a successfully treated case of fungal endophthalmitis, offering insights into clinical management. A 35-year-old female experienced decreased vision in her right eye following fetal reduction surgery. Her best-corrected visual acuity was limited to 10 cm finger counting in the affected eye. Following systemic antifungal therapy combined with vitrectomy, her vision recovered significantly. Through a detailed case analysis and literature review, this study aims to guide clinical practice. In patients with suspected EFE, obtaining early vitreous samples for pathogen identification and initiating timely treatment is critical. Furthermore, early vitrectomy during disease progression, along with an appropriate dosage and duration of antifungal therapy, is essential for restoring visual function and preventing vision loss.Keywords: endogenous fungal endophthalmitis, fetal reduction surgery, vitrectomy